2002
DOI: 10.1139/t02-005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the uplift behaviour of circular plate anchors embedded in sand

Abstract: An experimental investigation of the uplift behaviour of relatively large scale model circular plate anchors up to 400 mm in diameter embedded in loose, medium-dense, and dense dry sand is described. Uplift capacity is strongly influenced by anchor diameter, embedment ratio, and sand density. In tests on shallow half-cut models, a gently curved rupture surface emerged from the top edge of the anchor to the sand surface at approximately ϕ/2 to the vertical, where ϕ is the angle of shearing resistance. For a dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
50
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(61 citation statements)
references
References 21 publications
9
50
0
2
Order By: Relevance
“…This may in part explain the discrepancy between the numerical lower bounds and Pearce's results at larger embedment ratios. Also shown in (Figure 9(b)) are the chamber test results of Ilamparuthi, Dickin and Muthukrisnaiah (2002). These chamber tests results compare more favourably to the numerical results than those of Pearce (2000).…”
Section: Circular Anchorssupporting
confidence: 67%
“…This may in part explain the discrepancy between the numerical lower bounds and Pearce's results at larger embedment ratios. Also shown in (Figure 9(b)) are the chamber test results of Ilamparuthi, Dickin and Muthukrisnaiah (2002). These chamber tests results compare more favourably to the numerical results than those of Pearce (2000).…”
Section: Circular Anchorssupporting
confidence: 67%
“…There will also be some contribution from the shaft friction below the bottom plate and (for compression) a contribution from end bearing on the pile. A considerable amount of work is available to aid development of design approaches (for example, uplift plate factors from Merifield [12] or Llamparuthi et al [13]), and standard calculation approaches from the American Petroleum Institute or Det Norske Veritas pile design methods may also be applicable [14,15]. For pullout in undrained soils, there needs to be a careful consideration of the response at the base of the pile, particularly if the water depths are sufficiently shallow that cavitation may occur.…”
Section: Design Methodsmentioning
confidence: 99%
“…3) for plate anchors were deduced by trials and error from Eq. 33 using the pullout capacity results of Ilamparuthi et al (2002). The different values of this constant for plate anchors were also given in Fig.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Meyerhof and Adams (1968) proposed a value for the base angle (h 1 ) of the failure plane with the vertical in the range of u/4-u/2. While a value of u/2 has been proposed by Clemence and Veesaert (1977), Murray and Geddes (1987), and Ilamparuthi et al (2002). Based on the experimental results, Ghaly et al (1991) suggested a value for the angle h 1 as 2u/ 3 for shallow anchors.…”
mentioning
confidence: 92%
See 1 more Smart Citation